Current status of perioperative nutritional intervention and exercise in gastric cancer surgery: A review. Issue 2 (26th October 2021) - Ida, Satoshi; Kumagai, Koshi; Nunobe, Souya
Abstract: Patients with gastric cancer are often malnourished or sarcopenic during tumor progression. Perioperative malnutrition, including sarcopenia, is strongly related to postoperative complications and long‐term outcomes. To improve outcomes, nutritional intervention is common for patients with gastric cancer, especially for those undergoing elective surgery. Several clinical trials evaluating perioperative nutritional intervention have set postoperative loss of body weight and lean body mass as endpoints; however, the results were inconsistent. Therefore, recently, perioperative multimodal interventions that are expected to have a synergistic effect between nutritional intervention and exercise have gained attention. Furthermore, supplementing with leucine, a branched‐chain amino acid, in addition to exercise, may be promising for preventing perioperative sarcopenia. However, whether perioperative nutritional intervention and exercise has clinical benefits in gastric surgery is unclear. With the aging of gastric cancer patients, measures to address sarcopenia will become more important in the future. Understanding the significance of nutritional intervention and exercise in patients undergoing gastric cancer surgery will help achieve good outcomes. Abstract : The purpose of this review was to summarize the current evidence for perioperative nutritional intervention and exercise for gastrectomy. The particular focus is on measures of preventing sarcopenia perioperatively.